Social Facilitation of Cognition in Rhesus Monkeys: Audience Vs. Coaction - Reynaud, Amélie J.; Guedj, Carole; Hadj-Bouziane, Fadila; Meunier, Martine; Monfardini, Elisabetta (Frontiers in Behavioral Neuroscience, 2015)
Social psychology has long established that the mere presence of a conspecific, be it an active co-performer (coaction effect), or a passive spectator (audience effect) changes behavior in humans. Yet, the process mediating this fundamental social influence has so far eluded us. Brain research and its nonhuman primate animal model, the rhesus macaque, could shed new light on this long debated issue. For this approach to be fruitful, however, we need to improve our patchy knowledge about social presence influence in rhesus macaques. Here, seven adults (two dyads and one triad) performed a simple cognitive task consisting in touching images to obtain food treats, alone versus in presence of a co-performer or a spectator. As in humans, audience sufficed to enhance performance to the same magnitude as coaction. Effect sizes were however 4 times larger than those typically reported in humans in similar tasks. Both findings are an encouragement to pursue brain and behavior research in the rhesus macaque to help solve the riddle of social facilitation mechanisms.